Cerebral Ischemia 2021
DOI: 10.36255/exonpublications.cerebralischemia.2021.curcumin
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Curcumin in Post-Ischemic Brain

Abstract: Progressive accumulation of misfolded amyloid and tau protein in intracellular and extracellular spaces is the most crucial etiopathological feature of brain ischemia, synaptic damage, or neural communication impairment. Clinical data suggest that dietary intake of curcumin enhances neurogenesis and offers neuroprotection. Curcumin is a natural polyphenolic compound with diverse and attractive biological properties. It may prevent aging-associated changes in cellular proteins, such as β-amyloid peptide and tau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 109 publications
(167 reference statements)
1
2
0
Order By: Relevance
“…Curcumin is a bioactive compound with significant antiinflammatory, antiapoptotic, and antioxidant properties. This results in agree to previous studies stating curcumin as a traditional medicine has anti-infl ammatory, anti-infective, antitumor, antibacterial, and antioxidant properties, and is believed to have a positive effect on ischemic stroke (Goozee et al, 2016;Hagl et al, 2015;Manca et al, 2015;Park et al, 2021;Rusek & Czuczwar, 2021). The anti-inflammatory, antioxidant and neuroprotective properties contained in curcumin help control ischemic stroke by preventing more severe brain impact (Ułamek-Kozioł et al, 2020).…”
Section: Curcumin Reduces Neurological Defi Citssupporting
confidence: 92%
See 2 more Smart Citations
“…Curcumin is a bioactive compound with significant antiinflammatory, antiapoptotic, and antioxidant properties. This results in agree to previous studies stating curcumin as a traditional medicine has anti-infl ammatory, anti-infective, antitumor, antibacterial, and antioxidant properties, and is believed to have a positive effect on ischemic stroke (Goozee et al, 2016;Hagl et al, 2015;Manca et al, 2015;Park et al, 2021;Rusek & Czuczwar, 2021). The anti-inflammatory, antioxidant and neuroprotective properties contained in curcumin help control ischemic stroke by preventing more severe brain impact (Ułamek-Kozioł et al, 2020).…”
Section: Curcumin Reduces Neurological Defi Citssupporting
confidence: 92%
“…It has high antioxidant properties, anti-infl ammatory properties, anti-apoptosis, and is able to protect the blood brain barrier (BBB). In addition, many studies showed that curcumin plays role in promoting neurogenesis and as neuroprotection useful for repairing brain cells in ischemic stroke patients Li et al, 2015;Rusek & Czuczwar, 2021;Ułamek-Kozioł et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation